Role of acupuncture in the treatment of insulin resistance: A systematic review and meta-analysis. (November 2019) - Wu, Liqun; Chen, Xiaokun; Liu, Yun; Lan, Jiao; Wu, Chunxiao; Li, Zhixing; Lu, Liming; Yi, Wei
Abstract: Background: and purpose Acupuncture has gained increasing attention in the treatment of insulin resistance (IR). This study systematically reviews the efficacy of acupuncture on clinical IR outcomes. Methods: Cochrane Central Register of Controlled Trials, Embase, Medline (via OVID), China National Knowledge Infrastructure (CNKI), Wan Fang and China Science and Technology Journal Database (VIP) were searched to collect randomized controlled trials (RCTs) of patients with IR treated by acupuncture. Meta-analysis was performed by RevMan 5.3. Results: With acupuncture, the homeostasis model assessment of insulin resistance (homa-IR) significantly decreased (mean difference (MD) = -1.04, 95% confidence interval (CI) −1.37 to −0.71; P < 0.00001), as did fasting blood glucose (FBG) (MD = −0.56, 95% CI -0.88 to −0.25; P = 0.0005), 2 h postprandial blood glucose (2hPG) (MD = −0.91, 95% CI -1.62 to −0.20; P = 0.01), and fasting insulin (FINS) (MD = −3.23, 95% CI -4.14 to −2; P < 0.00001). Meanwhile, the insulin sensitivity index (ISI) (MD = 0.36, 95% CI 0.18 to 0.53; P < 0.0001) increased, and fewer adverse events occurred. Conclusion: Acupuncture may improve homa-IR, ISI, FBG, 2hPG and FINS with fewer adverse events than other treatments, making it a viable treatment for IR. Highlights: 20 RCTs that reported the effectiveness of acupuncture treating diseases related to insulin resistance were included. This study found that acupuncture is better to act as an adjuvant therapy for the management of IR than as a replacement. Analyses showed that acupuncture had an advantage over control groups in decreasing FBG, 2hPG and FINS levels. The pooled analysis showed that acupuncture alone was more effective than sham acupuncture at decreasing homa-IR levels. Acupuncture was well tolerated by patients, with fewer adverse events than Western medicine.